The evaluation of L-arginine solution as a solvent for propolis extraction: The phenolic profile, antioxidant, antibacterial activity, and in vitro bioaccessibility - Duymaz, Gizem Mergen; Duz, Gamze; Ozkan, Kubra; Karadag, Ayse; Yilmaz, Ozlem; Karakus, Ayca; Cengiz, Ozlem; Akyildiz, Ismail Emir; Basdogan, Gunay; Damarli, Emel; Sagdic, Osman (WILEY, 2024)
Ethanol has been widely used for the extraction of propolis. Due to its certain disadvantages, there has been an ongoing search to find alternative non-ethanolic extraction solvents. This study aimed to compare the phenolics, antioxidant, and antibacterial activity of propolis extracts prepared with 70% ethanol (EWE), propylene glycol (PGE), and L-arginine solution (BE). All extracts were subjected to an in vitro simulated digestion procedure, and the phenolic profile of non-digested and digested samples was determined by using LC-MS/MS. Additionally, the change in total phenolic (TPC), total flavonoid content (TFC), and antioxidant capacities were determined at each digestion phase. TPC and TFC of non-digested propolis extracts had similar values, although BE showed higher antioxidant capacity (p < .05). The amount of TPC reached or transformed at the intestinal stage was higher for BE and PG compared to EWE. BE also provided the highest antioxidant capacity assay in digested samples. The most common phenolics were pinocembrin, pinobanskin, galangin, and CAPE in non-digested extracts. However, their concentration was drastically reduced by digestion, and their recovery (R%) ranged from 0% to 9.38% of the initial amount detected in the non-digested extracts. Chrysin was the most bioaccessible flavonoid in all extracts. Among phenolic acids, the highest R% was determined for trans-cinnamic acid (22.14%) from BE. All extracts showed in vitro inhibitory activity against Escherichia coli and Staphylococcus aureus. This study suggests that an L-arginine solution could be used as an alternative solvent to ethanol and propylene glycol for propolis extraction.
Keywords: bioaccessibility; extraction; flavonoids; LC-MS/MS; ANTIMICROBIAL ACTIVITY; PH; Food Science & Technology